2001
DOI: 10.3168/jds.s0022-0302(01)74538-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mastitis in Dairy Heifers and Effectiveness of Antibiotic Therapy

Abstract: Dairy heifers were treated 0 to 90 d, 90 to 180 d, or 180 to 270 d prepartum with one of five different antibiotic products to determine the best time and with which product they should be treated prior to calving. Two hundred thirty-three heifers were included in the study. At the initial sampling, 56.5% of quarters were infected with some type of organism and 15.4% of quarters were infected with Staphylococcus aureus. Treatments included a cephapirin dry cow product, a penicillin-novobiocin dry cow product, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 6 publications
4
44
0
7
Order By: Relevance
“…Mastitis in heifers is becoming an important economic problem in dairy herds (Huijps et al, 2009), and prepartum incidence rates are high (39% to 75%; Oliver et al, 2004;Fox, 2009) in different countries, such as the United States of America (Pankey et al, 1991;Owens et al, 2001), Germany (Kromker and Friedrich, 2009), Norway (Waage et al, 1999), Denmark (Aarestrup and Jensen, 1997) and Turkey (Bastan et al, 2010). There is a need for accurate, rapid and inexpensive methods to screen for potential mastitis pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis in heifers is becoming an important economic problem in dairy herds (Huijps et al, 2009), and prepartum incidence rates are high (39% to 75%; Oliver et al, 2004;Fox, 2009) in different countries, such as the United States of America (Pankey et al, 1991;Owens et al, 2001), Germany (Kromker and Friedrich, 2009), Norway (Waage et al, 1999), Denmark (Aarestrup and Jensen, 1997) and Turkey (Bastan et al, 2010). There is a need for accurate, rapid and inexpensive methods to screen for potential mastitis pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Owens et al (2001), pengobatan menggunakan kombinasi antibiotik pencillinstreptomycin menunjukkan tingkat keberhasilan yang tinggi dalam menyembuhkan kasus mastitis pada ternak sapi perah. Penicillin merupakan antibiotik yang dapat membunuh bakteri gram positif (Rismardiati, 1985), sedangkan streptomycin efektif terhadap bakteri gram negatif penyebab mastitis (Suriyasathaporn, 2010).…”
Section: Pendahuluanunclassified
“…Previous studies also reported milk loss due to udder infection in crossbred cows -about 4.8 kg/ day and about 28.8 kg/case (Sharma, 2010) with 552 kg milk loss per lactation (Pal, 2003). Moreover previous studies revealed that Jersey heifers treated with Intramammary antibiotic prepartum produced 531 kg more milk per lactation compared to those without treatment (Oliver et al, 2003 andOwens et al, 2001) Milk composition: Effect of dry cow therapy on milk composition is presented in Table 3. There was no significant difference in milk composition (fat, protein and lactose) between treatment and control groups except that milk SNF and total solids (TS) differed significantly (P<0.05) between treated and control group during 3 rd fortnight only.…”
Section: Milk Productionmentioning
confidence: 99%